Penerapan Strategi Bauran Pemasaran Pada Restoran Xyz Di Jakarta Utara (Fakultas Ekonomi Universitas Gresik, 2023)
This study aims to find out what marketing mix strategies XYZ restaurants have carried out and to provide an overview of the strengths, weaknesses, opportunities and threats that XYZ restaurants will face. This research uses qualitative research with a descriptive approach, data collection is carried out by interviews, observations and documentation. The results of this study show the marketing mix strategy implemented by XYZ North Jakarta restaurants to attract consumers and increase restaurant sales. From the product aspect (Product) XYZ Restaurant serves the main products served are Kalasan Grilled Chicken and Kremes Fried Chicken. The attraction that affects consumers is that the price is quite affordable and a strategic place, besides being supported by a comfortable and clean place to eat. From the price aspect of XYZ restaurant, which can be said to be the cheapest among other similar competitors, restaurants must apply competitive prices, from the aspect of place (place) distribution channels, XYZ restaurants register with online ordering applications such as Go Food, Grab Food, Shopeefood, and We Help You to make it easier for consumers to make long-distance purchases. From the promotional aspect, the promotion carried out by the Saung Pooci restaurant is to put a banner on the front side of the restaurant that is visible from the road. Promotions are also carried out through instagram social media, as well as utilizing online ordering applications such as Go Food, Grab Food, Shopee Food and We Help Youwhich can reach more consumers and provide 10-60 percent promos on online orders. From the people aspect, this marketing mix emphasizes more on individual dexterity, responsiveness in consumer needs. In the process aspect (proces) provides convenience to consumers when making payments because this restaurant can make payments through shopeepay, ovo, and M-Banking. And provide free delivery for the surrounding area that is affordable. From the aspect of physical appearance (Physical evidance) provides a comfortable and clean place, as well as providing music to the room so that consumers relax. This restaurant also provides complete facilities such as parking lots, toilets and toilets.